Pengaruh Model Pembelajaran Inquiry terhadap Hasil Belajar IPA Siswa Kelas V SD Negeri 101739 Sei Mencirim - Nazaruddin, Ilham; Sari, Ery Novita; Mahmud, Ronald (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2024)
This research discusses the results of research using a quasi-experiment (Quasy Experiment) for the Influence of the Inquiry on the Science Learning Outcomes of Class V Students at SD Negeri 101739 Sei Mencirim TP 2024/2025 Student learning outcomes in the experimental class using the Inquiry model for the posttest obtained an average score of 80 and a complete KKM score, namely a frequency of 15 students with a percentage of 88.23%. There is an influence of the Inquiry model on the science learning outcomes of class V students with material magnetism and electricity in Class V SD Negeri 101739 Sei Mencirim TP 2024/2025, this is confirmed by the results of hypothesis testing with a sig value of 0.000.